Composer Gerardo Guevara in Ecuadorian musical nationalism. An analysis Fiesta for piano - Campos Serrano, Jorge (2019)
The present research studies one of the musical works that is most representative of the musician Gerardo Guevara, one of the most important Ecuadorian composers of the 20th century. The first part of the paper addresses the artistic trajectory and academic formation of the composer and, above all, aims to systematize the study of different stylistic periods suggested by his fruitful musical works. The paper additionally explores his particular forms of alignment with Ecuadorian musical nationalism and diverse strategies of composition that he used to create a syncretic musical work, Fiesta in the albazo style, in which the elements of an oral musical tradition acquire a meaning distanced from localizing and folklorizing tendencies. This research shows how the composer goes beyond popular Ecuadorian genres to create a previously inaudible musical universe, in which the use of musical elements, such as pentatonicism and musical form, generate new and transcendent works in constant search of “universality.” The second part of the paper addresses the analysis of Fiesta, an albazo musical piece written for piano, that demonstrates concretely the techniques employed by the composer in relation to melodic and harmonic aspects.